Paper-based selective and quantitative detection of uric acid using citrate-capped Pt nanoparticles (PtNPs) as a colorimetric sensing probe through a simple and remote-based device. (1st May 2019) - Ali, Muhsin; Khalid, Muhammad Asad Ullah; Shah, Imran; Kim, Soo Wan; Kim, Young Su; Lim, Jong Hwan; Choi, Kyung Hyung
Abstract : A colorimetric portable setup was developed for remote UA measurements using a smartphone-based application to demonstrate its use in point-of-care testing. Abstract : A colorimetric portable setup was developed for remote UA measurements using a smartphone-based application to demonstrate its use in point-of-care testing. Quantitative and affordable point-of-care health diagnostics is a rapidly evolving field using nanostructured materials for the detection of various disease biomarkers. The detection of uric acid is of great importance to identify many health syndromes and to avoid relevant complications. Herein, a selective, sensitive, and quantitative detection of uric acid on a cellulose fiber strip using citrate-capped platinum nanoparticles (PtNPs) as a nanozyme is reported for the first time. A reduction method was followed to synthesize the PtNPs (8–10 nm), which were characterized using UV-vis spectroscopy, XRD, and TEM to determine their properties. Morphological characterization of the cellulose substrate was performed using FESEM. A strip was developed having a circular shaped head of 8 mm diameter, which was pretreated with PVA, TMB + H2 O2, and PtNPs, respectively. In the presence of PtNPs (enzyme catalytic activity), TMB acted as a hydrogen donor to reduce H2 O2, giving a bluish-green color on the substrate. The developed method provided a wide linear response from 0 mM to 8 mM for uric acid samples, with the results indicating the downregulating activity of the PtNPs. A calculated LOD of 4.2 ± 5 μM was achieved and the results showed a linear response till 7 mM in terms of the color observation. In conclusion, the developed sensing system could be potentially applicable for the quantitative detection of uric acid in the physiological range in urine samples.